Supported cobalt catalysts by one-pot aqueous combustion synthesis for catalytic phenol degradation - Sun, Hongqi; Liang, Hanwen; Zhou, Guanliang; Wang, Shaobin (Academic Press, 2013)
Cobalt oxides (Co) and Al2O3-, SiO2-, and TiO2-supported cobalt oxide catalysts were prepared by anaqueous combustion method using urea and glycine as fuels. Their catalytic performance in activationof OXONE for phenol degradation in aqueous solution was investigated. It was found that unsupported Co oxide and supported Co oxide presented different mechanisms in activation of OXONE for phenol degradation. The supported Co catalysts presented higher activity in activation of OXONE for phenol degradation due to higher dispersion of Co3O4 on the supports and Co(II) coordination sites. The major oxidizing radicals were identified to be SO4- by competitive radical reactions. The Co oxides synthesized from urea or glycine showed a similar activity; however, the supported Co catalysts prepared by glycine fuel exhibited better activity than those prepared by urea. For Al2O3-, SiO2-, and TiO2-supported Co catalysts, Co/TiO2 presented a higher activity in phenol degradation compared with Co/SiO2 and Co/Al2O3. But, Co/SiO2 showed the best stability among the catalysts. Total organic carbon could be reduced by 80%, 72%, and 45% on Co/TiO2, Co/SiO2, and Co/Al2O3, respectively, at 30 ppm phenol. Phenol degradation was found to follow the zero-order kinetics. The causes of deactivation were investigated, and the regeneration methods were proposed.